Managing the dominant follicle in lactating dairy cows - Wiltbank, M. C.; Sartori, R.; Herlihy, M. M.; Vasconcelos, José Luiz Moraes [UNESP]; Nascimento, A. B.; Souza, A. H.; Ayres, H.; Cunha, A. P.; Keskin, A.; Guenther, J. N.; Gumen, A. (Elsevier B.V., 2011)
Reproductive efficiency is not optimal in high-producing dairy cows. Although many aspects of ovarian follicular growth in cows are similar to those observed in heifers, there are numerous specific differences in follicular development that may be linked with changes in reproductive physiology in high-producing lactating dairy cows. These include: I) reduced circulating estradiol (E2) concentrations near estrus, 2) ovulation of follicles that are larger than the optimal size, 3) increased double ovulation and twinning, and 4) increased incidence of anovulation with a distinctive pattern of follicle growth in anovular dairy cows. The first three changes become more dramatic as milk production increases, although anovulation has not generally been associated with level of milk production. To overcome reproductive inefficiencies in dairy cows, reproductive management programs have been developed to synchronize ovulation and enable the use of timed AI in lactating dairy cows. Effective regulation of the CL, follicles, and hormonal environment during each part of the protocol is critical for optimizing these programs. This review discusses the distinct aspects of follicular development in lactating dairy cows and the methodologies that have been utilized in the past two decades in order to manage the dominant follicle during synchronization of ovulation and timed AI programs. (C) 2011 Published by Elsevier B.V.
Keywords: Follicle; Dairy cattle; Ovsynch; Synchronization of ovulation; Timed AI